2006
DOI: 10.1111/j.1445-5994.2006.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab use in systemic lupus erythematosus pneumonitis and a review of current reports

Abstract: Rituximab is a chimeric monoclonal antibody specific for human CD20 that causes selective transient depletion of the CD20+ B-cell subpopulation. We report the first case of systemic lupus erythematosus (SLE) pneumonitis resistant to conventional treatments that responded well to rituximab and review current reports on the use of rituximab in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 13 publications
(31 reference statements)
0
17
0
1
Order By: Relevance
“…Although there are no published trials on the use of rituximab for RA-ILD, Popa et al found that RA patients treated with rituximab for 7 years have not shown any evidence of new RA-ILD [97]. There are also several cases reporting the successful use of weekly rituximab for ILD in other forms of collagen vascular disease [98101]. …”
Section: Other Possible Drug Therapiesmentioning
confidence: 99%
“…Although there are no published trials on the use of rituximab for RA-ILD, Popa et al found that RA patients treated with rituximab for 7 years have not shown any evidence of new RA-ILD [97]. There are also several cases reporting the successful use of weekly rituximab for ILD in other forms of collagen vascular disease [98101]. …”
Section: Other Possible Drug Therapiesmentioning
confidence: 99%
“…Although data in SLE patients are limited, steroid sparing agents like cyclophosphamide, azathioprine, mycophenolate, rituximab have been used in the past. [11] …”
Section: Discussionmentioning
confidence: 99%
“…If there is no prompt improvement, then intravenous methylprednisolone with an immunosuppressive agent such as cyclophosphamide is commonly used. One report described a patient with acute lupus pneumonitis who responded to weekly rituximab with a rapid improvement in subjective symptoms and pulmonary function test abnormalities [84]. …”
Section: Other Connective Tissue Disease-associated Interstitial Lungmentioning
confidence: 99%